2008
DOI: 10.1088/0031-9155/53/10/n03
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo dose calculation of segmental IMRT delivery to a moving phantom using dynamic MLC and gating log files

Abstract: Respiratory gating is emerging as a tool to limit the effect of motion for liver and lung tumors. In order to study the impact of target motion and gated intensity modulated radiation therapy (IMRT) delivery, a computer program was developed to simulate segmental IMRT delivery to a moving phantom. Two distinct plans were delivered to a rigid-motion phantom with a film insert in place under four conditions: static, sinusoidal motion, gated sinusoidal motion with a duty cycle of 25% and gated sinusoidal motion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Qian et al (7) observed gamma passing rates >95% using only sinusoidal breathing traces for VMAT plans delivered on a TrueBeam linac. Similar dosimetric results were reported by Oliver et al (11) for IMRT plans delivered on a Varian 2100 C/D. One observation of note by Riley et al (13) was that irregular breathing could be responsible for poor dosimetric results seen in his phase gated study.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Qian et al (7) observed gamma passing rates >95% using only sinusoidal breathing traces for VMAT plans delivered on a TrueBeam linac. Similar dosimetric results were reported by Oliver et al (11) for IMRT plans delivered on a Varian 2100 C/D. One observation of note by Riley et al (13) was that irregular breathing could be responsible for poor dosimetric results seen in his phase gated study.…”
Section: Discussionsupporting
confidence: 80%
“…No trend is seen with PTV volume, for volumes ranging from 60 cc to 2388 cc. Our study was based on actual patient breathing traces, while most previous studies 7 , 11 , 13 used a sinusoidal breathing pattern, which may mask problems associated with realistic breathing patterns. These previous studies also used a phase gating approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fixed-duty cycle experiments, the efficacy of duty cycles ranging from 20% to 50% have been studied. 1,9,11,15,21,22,24,[26][27][28] In experiments with fixed gating windows, duty cycles ranging from 12.2% to 69% have been seen. 4,7,8,17,20 Various studies have sought to improve the performance of respiratory gating by provid-ing audio or visual coaching to patients so as to increase the reproducibility and stability of their breathing patterns, especially while the tumor is in the gating window.…”
Section: Introductionmentioning
confidence: 98%